ANALISIS KUALITAS AIR DAN BEBAN PENCEMAR DI SUNGAI BATU KAMBING, SUNGAI MALI-MALI DAN SUNGAI RIAM KIWA KECAMATAN ARANIO KABUPATEN BANJAR KALIMANTAN SELATAN - Chiptya Adhey Noumy; Zairina Yasmi; Abdur Rahman (Fish Scientiae, 2019)
This study aims to determine the water quality of the activities Keramba JaringApung (KJA) based on Pollutant Index and Air Quality Standard Quality specified in PP.82/2001 on Watershed of Batu Kambing, Riam Kiwa and Mali-Mali.This study uses pollutant load analysis and Pollutant Index based Kep.MenLH No.115 of 2003, Kep.MenLH No. 110/2003 on Based Determination of Water Pollution loadon Water Resources and laboratory analysis.From the research results Pollutant Load (BP) of each - each station are: Station 1(Batu Kambing) PO4 levels ranging from 0.40 kg/day and NO3 ranging from 0.36 kg/day.Station 2 (Riam Kiwa) for PO4 levels ranging from 0.42 kg/day and NO3 ranging from 0,012 kg/day. Station 3 (Mali – Mali river) PO4 levels ranging from 1.27 kg/day, whileNO3 ranging from 0.11 kg/day. Batu Kambing river, Riam Kiwa and Mali – Mali rivers included in the category of lightly polluted.